PENGARUH KOMPETENSI, DISIPLIN DAN MOTIVASI TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN, PENELITIAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN MOROWALI - Beti, Elinar (Katalogis, 2016)
The intention of this research are: 1) to test and analyze the simultaneous influence of competency, discipline, and motivation on employees’ performance in The Agency of Palanning, Research, and regional development, Morowali regency; 2) to test and analyze significant influence of competency on civil servants’ performance; 3) to test and analyze significant influence of discipline on civil servants’ performance; 4) to test and anlyze significant influence of motivation on civil servants’ performance. Population in this research consists of 42 civil servants in the The Agency planning, Research, and Regional Development (BAPPEDA), Morowali Regency, who are selected by census method. Multiple linear regressions test shos that: 1) competency, discipline, and motivation simultaneously have influence on employees’ performance in The Agency of Planning, Research, and Regional development, Morowali Regency; 2) competency, discipline, and motivarion partially have influence on employees’ performance in The Agency of Planning, Research, and Regional Development Morowali Regency. Determinant coefficient value of adjusted R² obtained is 0,756; it means that 75,6% of variable performance is influenced by competency, discipline, and motivation and the remaining of 24,4% influenced by other independent variables that are not studied.